“Not There as Strangers or Silent Spectators”:: Lay-led Virtual Liturgies in the Spirit of Sacrosanctum Concilium - Julia Erdlen, (Lumen et Vita, 2020)
What is Holy Thursday with no Eucharist to break and share? What is the sign of peace with no physical embrace? What is a Catholic, Sunday service without a priest, deacon, or consecrated hosts? Six months ago, these were hypothetical questions reserved for academics, for sacramental and liturgical theologians. In March, these became the questions of every Catholic who could no longer inhabit the pews of their church. Many churches quickly adapted to the pandemic with the practice of live streaming or uploading videos of the Sunday Mass, with the only difference in the service being the lack of a congregation and choir. These churches sought to provide ‘the same’ Sunday services under unprecedented circumstances and with little previous experience with online worship. However, a streamed mass could not possibly be the same for the laity without physical participation, the call and response between the priest and the assembly, and the reception of the Eucharist. This paper argues that virtual, interactive, lay- led Sunday services can more faithfully imitate the spirit of the Vatican II document, Sacrosanctum Concilium, in fostering the full and active participation of the assembly than streamed or pre-recorded masses. Despite being a departure from what was previously considered acceptable Sunday worship, in the time of pandemic there are broad dispensations from the obligations of the faithful to attend a Sunday mass. Therefore, lay Catholics are not restricted to a binary choice between viewing mass in a physical or virtual way, and have the freedom to seek out opportunities to pray together in ways that foster their full and active participation in Sunday worship.